Screening for autism spectrum disorder in underserved communities: Early childcare providers as reporters. (April 2016) - Janvier, Yvette M; Harris, Jill F; Coffield, Caroline N; Louis, Barbara; Xie, Ming; Cidav, Zuleyha; Mandell, David S
Early diagnosis of autism typically is associated with earlier access to intervention and improved outcomes. Daycares and preschools largely have been ignored as possible venues for early identification. This may be especially important for minority children in the United States who are typically diagnosed with autism later than White children, limiting their access to early specialized interventions and possibly resulting in poorer outcomes. Early childcare providers within underserved communities completed autism screening tools for a sample of low-risk young children ( n  = 967) in their programs. Early childcare providers returned screening tools for 90% of the children for whom parental consent had been received. A total of 14% of children screened positive for autism spectrum disorder and 3% of the sample met criteria for autism spectrum disorder. Among those who screened positive, 34% were lost to follow-up. Findings suggest that early childcare providers can effectively screen young children for autism spectrum disorder in preschool/daycare settings, thus improving access to early diagnosis and reducing potential healthcare disparities among underserved populations.